The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11920-009-0073-2
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity in mania

Abstract: Impulsivity, a breakdown in the balance between initiation and screening of action that leads to reactions to stimuli without adequate reflection or regard for consequences, is a core feature of bipolar disorder and is prominent in manic episodes. Catecholaminergic function is related to impulsivity and mania. Manic individuals have abnormal dopaminergic reactions to reward and abnormal responses in the ventral prefrontal cortex that are consistent with impulsive behavior. Impulsivity in mania is pervasive, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 60 publications
3
38
0
1
Order By: Relevance
“…Similarly, considering that impulsivity is an important factor in suicidal behavior (41), the COMT Met allele has been reported to be a risk factor for suicide in men but not in women (42,43). The COMT Met allele has also been associated with increased aggressive behavior in men (44), which may be another reflection of impulsivity (40,41). In agreement with these human studies and paralleling our present data, male mice with reduced COMT show increased aggressive behavior (1).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, considering that impulsivity is an important factor in suicidal behavior (41), the COMT Met allele has been reported to be a risk factor for suicide in men but not in women (42,43). The COMT Met allele has also been associated with increased aggressive behavior in men (44), which may be another reflection of impulsivity (40,41). In agreement with these human studies and paralleling our present data, male mice with reduced COMT show increased aggressive behavior (1).…”
Section: Discussionsupporting
confidence: 90%
“…It is interesting to note that response-inhibition deficits are present in OCD (40), and that the COMT Met polymorphism (i.e., reduced COMT activity) has been consistently associated with increased risk for OCD in men but not in women (26,27). Similarly, considering that impulsivity is an important factor in suicidal behavior (41), the COMT Met allele has been reported to be a risk factor for suicide in men but not in women (42,43). The COMT Met allele has also been associated with increased aggressive behavior in men (44), which may be another reflection of impulsivity (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…In a dimensional perspective, even modest manic symptoms could increase levels of state impulsivity enough to be detectable by behavioural task, in line with the data previously reported in the literature (Swann A. C., Moeller F.G. et al 2007;Swann 2009). …”
Section: Discussionsupporting
confidence: 90%
“…These studies have found evidence for steeper discounting amongst patients with symptoms of schizophrenia (Heerey et al, 2007(Heerey et al, , 2011Ahn et al, 2011;MacKillop and Tidey, 2011;Wing et al, 2012;Avsar et al, 2013;Weller et al, 2014), depression (Takahashi et al, 2008;Dennhardt and Murphy, 2011;Dombrovski et al, 2012;Imhoff et al, 2014;Pulcu et al, 2014), mania (Mason et al, 2012), attention deficit hyperactivity disorder (ADHD) (Barkley et al, 2001;Tripp and Alsop, 2001;Bitsakou et al, 2009;Paloyelis et al, 2010a,b;Scheres and Hamaker, 2010), anxiety disorder and cluster B personality disorder (Dougherty et al, 1999;Moeller et al, 2002;Petry, 2002;Dom et al, 2006a,b;Lawrence et al, 2010;Coffey et al, 2011). This line of enquiry is not without theoretical justification, for example the broader construct of impulsivity, defined as taking action without forethought or regard for consequences (Moeller et al, 2001), of which discounting is an element, is a defining feature of some psychiatric disorders, for example borderline personality disorder (Moeller et al, 2001;DSM V, 2013) and mania (Swann, 2009). Also, psychiatric disorders are strongly associated with poor health choices, including but not limited to cigarette smoking, and drug and alcohol misuse (Robson and Gray, 2007), which have themselves been associated with steeper discounting (Bickel et al, 2012b(Bickel et al, , 2014aStory et al, 2014).…”
Section: Vitae Summa Brevis Spem Nos Vetat Incohare Longammentioning
confidence: 99%
“…We propose that the pathological state of mania is associated with perceived high rates of reward and high growth potential, creating a heightened opportunity cost associated with inaction. Mania is known to be associated with impulsive behavior, such as overspending, rash financial decision-making or drug-taking (Swann, 2009), and one study (Mason et al, 2012) finds evidence for steeper discounting in an intertemporal choice task with real-time delays in the order of seconds in individuals prone to hypomanic symptoms.…”
Section: Mania As a State Of Increased Opportunity Costmentioning
confidence: 99%